Pt-nanoparticle functionalized carbon nano-onions for ultra-high energy supercapacitors and enhanced field emission behaviour - Suryawanshi, Sachin R.; Kaware, Vaibhav; Chakravarty, Disha; Walke, Pravin S.; More, Mahendra A.; Joshi, Kavita; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2015)
In the present work, we have investigated the charge storage capacitive response and field emission behaviour of platinum (Pt) nanoparticles decorated on carbon nano onions (CNOs) and compared them with those of pristine carbon nano onions. The specific capacitance observed for Pt-CNOs is 342.5 F g(-1), about six times higher than that of pristine CNOs, at a scan rate of 100 mV s(-1). The decoration with Pt nanoparticles, without any binder or polymer separator on the CNO, leading to enhanced supercapacitance is due to easy accessibility of Na2SO4 electrolyte in the active material. The Density Functional Theory (DFT) calculations of these systems reveal enhancement in the Density of States (DOS) near the Fermi energy (E-F) on account of platinum decoration on the CNOs. Furthermore, the field emission current density of similar to 0.63 mA cm(-2) has been achieved from the Pt-CNOs emitter at an applied electric field of similar to 4.5 V mu m(-1) and from the pristine CNOs sample current density of similar to 0.4 mA cm(-2) has been achieved at an applied electric field of similar to 6.6 V mu m(-1). The observed enhanced field emission behavior has been attributed to the improved electrical conductivity and increased emitting sites of the Pt-CNO emitter. The field emission current stability of the Pt-CNO emitter over a longer duration is found to be good. The observed results imply multifunctional potential of Pt-CNOs, as supercapacitor material in various next generation hybrid energy storage devices, and field emitters for next generation vacuum nano/microelectronic devices.

Pulsed laser-deposited nanocrystalline GdB6 thin films on W and Re as field emitters - Suryawanshi, Sachin R.; Singh, Anil K.; Phase, Deodatta M.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (Applied Physics A-Materials Science & Processing, 2016)
Gadolinium hexaboride (GdB6) nanocrystalline thin films were grown on tungsten (W), rhenium (Re) tips and foil substrates using optimized pulsed laser deposition (PLD) technique. The X-ray diffraction analysis reveals formation of pure, crystalline cubic phase of GdB6 on W and Re substrates, under the prevailing PLD conditions. The field emission (FE) studies of GdB6/W and GdB6/Re emitters were performed in a planar diode configuration at the base pressure similar to 10(-8) mbar. The GdB6/W and GdB6/Re tip emitters deliver high emission current densities of similar to 1.4 and 0.811 mA/cm(2) at an applied field of similar to 6.0 and 7.0 V/mu m, respectively. The Fowler-Nordheim (F-N) plots were found to be nearly linear showing metallic nature of the emitters. The noticeably high values of field enhancement factor (beta) estimated using the slopes of the F-N plots indicate that the PLD GdB6 coating on Wand Re substrates comprises of high-aspect-ratio nanostructures. Interestingly, the GdB6/W and GdB6/Re planar emitters exhibit excellent current stability at the preset values over a long-term operation, as compared to the tip emitters. Furthermore, the values of workfunction of the GdB6/W and GdB6/Re emitters, experimentally measured using ultraviolet photoelectron spectroscopy, are found to be same, similar to 1.6 +/- 0.1 eV. Despite possessing same workfunction value, the FE characteristics of the GdB6/W emitter are markedly different from that of GdB6/Re emitter, which can be attributed to the growth of GdB6 films on W and Re substrates.